Aging and Alzheimer’s: the critical role of mitochondrial dysfunction and synaptic alterations - Pinky; Wali, Zitin; Neha; Tiwari, Prachi; El-Tanani, Mohamed; Rabbani, Syed Arman; Parvez, Suhel (Frontiers in Synaptic Neuroscience, 2026)
Alzheimer’s disease is a progressive neurodegenerative disorder marked by cognitive decline, accumulation of amyloid-β plaques and neurofibrillary tangles, synaptic dysfunction, and mitochondrial impairment. Despite multiple therapeutic strategies, currently available treatments only provide symptomatic relief without halting disease progression. Emerging evidence implicates mitochondrial dysfunction–including oxidative stress, impaired calcium signaling, mitophagy deficits, disrupted proteostasis, and electron transport chain abnormalities, as central to AD pathogenesis. These dysfunctions contribute to synaptic degeneration, increased reactive oxygen species, and neuronal death. This review consolidates current knowledge on the mechanistic pathways of mitochondrial impairment in AD and their downstream effects on neuronal health. We also explore the therapeutic potential of multitarget approaches, including agents targeting Aβ and tau pathology, oxidative stress mitigation, mitochondrial quality control, and synaptic restoration. By integrating evidence from recent preclinical and clinical studies, this work highlights mitochondrial homeostasis as a promising frontier for disease-modifying therapies in AD.